Intervention based on the family health nurse model on the anthropometric and glycemic indicators of middle-aged prediabetics: Protocol for a randomized clinical trial (RCT) - Mohammad Azadmanesh; Mahrokh Keshvari; Ziba Farajzadegan; Atefeh Afshari (Journal of Education and Health Promotion)
BACKGROUND: Diabetes and prediabetes are some of the most prevalent and expensive diseases. The role and support of the family are some of the most helpful variables in managing and preventing diabetes and prediabetes. The aim of this study is to examine the intervention based on the family health nurse model on the anthropometric and glycemic indicators of middle-aged prediabetics. MATERIALS AND METHODS: This randomized clinical trial study will be conducted from January to March 2024 in selected healthcare facilities in Isfahan City. Using a table of random numbers, 72 eligible people will be randomly selected from the intervention and control centers to participate in the study. After getting written consent, a list of the families’ health-related issues, resources, and challenges will be gathered by visiting the clients’ homes. Then, family health nurse model-based interventions are put into place for them. By carrying out the necessary tests, information will be gathered. Software called SPSS 26 will be used for data analysis. CONCLUSION: Determining the effectiveness of the Family Health Nurse (FHN) model on the control and prevention of diabetes can offer a suitable framework for providing family-oriented services to middle-aged people with prediabetes and improving their health by considering social factors, such as family.